Comparison between 10 and 12 mg doses of intrathecal hyperbaric (0.5%) bupivacaine on sensory block level after first spinal failure in cesarean section: A double-blind, randomized clinical trial - Manouchehrian, Nahid; Rahimi-Bashar, Farshid; Pirdehghan, Azar; Shahmoradi, Fatemeh (Frontiers in Medicine, 2022)
ABSTRACT Background: Reducing adverse effects during cesarean delivery and improving the quality of sensory blocks with appropriate doses of intrathecal hyperbaric bupivacaine can play an important role in the safe management of cesarean delivery. The aim of this study was to compare the doses of 10 and 12 mg of intrathecal hyperbaric bupivacaine 0.5% on sensory block level after first spinal failure in cesarean section (CS). Methods: In this double-blind, randomized clinical trial, 40 candidates of CS after first spinal failure with class I‑II based on American Society of Anesthesiologists (ASA) were randomly assigned into two equal groups (n=20). Group A and B received the spinal anesthesia with 10 mg and 12 mg of hyperbaric bupivacaine (0.5%), respectively. Maximum levels of sensory block, motor block quality, and vital signs were measured in two groups by 60 minutes after SPA. Incidence of PDPH and SPA complications during surgery were also recorded. Data were analyzed by SPSS ver.21 software using repeated measures analysis of variance at 95% confidence interval (CI) level. Results: Excellent quality of sensory blocks and complete quality of motor blocks were achieved in all participants (100%). However, the mean time to onset of anesthesia (4.47±0.69 vs. 3.38±0.47, P<0.001) and time to reach T10 level (60.73±11.92 vs. 79.00±19.21, P<0.001) in the Group A, were significantly shorter than in the patients of Group B. The incidence of hypotension (P=0.001), nausea/vomiting (P=0.007) and bradycardia (P=0.012) as well as administration of ephedrine and atropine were significantly higher in Group B compared to Group A. Conclusion: Spinal anesthesia can be safely repeated with a 10 mg of hyperbaric bupivacaine 0.5% in a caesarean section after the initial spinal failure.